Development and Validation of ADI-STEM-Based Biotechnology e-Liveworksheets to Enhance Student Argumentation Skills - Hasnunidah, Neni; Fadiawati, Noor; Herlina, Kartini; Dewi, Pramita Sylvia (Jurnal Pendidikan MIPA, 2025)
Development and Validation of ADI-STEM-Based Biotechnology e-Liveworksheets to Enhance Student Argumentation Skills. Objectives: Despite its enormous potential, ADI-STEM-based electronic worksheets are still rarely used. In the face of the challenge of integrating STEM, ADI-based worksheets should be centered on authentic engineering issues. Designing real-world, challenging, yet still solvable problems for students with digital tools (Technology & Math) and relevant Science concepts. The purpose of this study is to fill this gap by developing and validating a reliable teaching material called the ADI-STEM-Based Biotechnology e-Liveworksheets (ASBL), which is intended to train the argumentation skills of Indonesian junior high school students. Methods: The research employed a development method using the Thiagarajan 4-D model, which includes the stages of Define, Design, and Develop, without the Disseminate stage. The ASBL underwent rigorous validation by experts and field testing in junior high school students in Indonesia. The Sampson & Clark framework is used to measure students' argumentative skills. Two biology education experts reviewed the content to ensure its validity. Two media experts reviewed the content to ensure its validity, and a senior teacher assessed the feasibility and practicality of ASBL. Researchers got real-world data for descriptive-quantitative analysis from 30 9th-grade students at a junior high school in Lampung, Indonesia. This data demonstrates the practicality of teaching materials, as evidenced by the increase in the average value of argumentation skills between before and after learning, as well as the responses of educators and students to the learning process. Data were collected using validated questionnaires and written tests. Findings: The results of the study showed that the ASBL was stated as very high validity (93%) by material experts, high validity (87%) by media experts, very practical to uses in learning by students (98%), with in improving students’ argumentation skills with N-gain in the high cateogry of claim (0,82), evidence (0,78), and reasoning (0,79). The majority of students (over 85%) found ASBL easy to use, engaging, and helpful in guiding their learning process. Teachers reported that the platform enabled efficient progress tracking and assessment of students’ argument construction at each learning phase. Conclusion: This research develops valuable and valid teaching materials to train students' argumentation skills. As a teaching material that aligns with the Independent Curriculum, ASBL is quite useful for Indonesian teachers. This encourages a shift from memorizing things by rote to understanding them more deeply and learning how to conduct science. Future research could explore scaling this model across different science topics, educational levels, or through longitudinal studies to assess retention and transfer of argumentation skills.     Keywords: biotechnology, liveworksheets, argumentation, argument-driven inquiry, STEM.